2008
DOI: 10.1177/1756283x08096285
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal Dieulafoy's lesions and endoscopic treatment: First report from a Mexican centre

Abstract: Abstract:The aim was to evaluate the initial success, rebleeding rate, need for emergent surgery, and mortality rates of patients with Dieulafoy's lesion (DL) and endoscopic treatment (ET). Patients with DL from a tertiary center were included. We included 20 patients with follow-up of 90 (60-550) days. The lesser curvature was the most common localization. Initial success, rebleeding, and emergent surgery requirement were observed in 90%, 10%, and 15%, respectively. No objective variables were related with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
(29 reference statements)
0
8
0
2
Order By: Relevance
“…Therefore, multiple endoscopies are often necessary to make the diagnosis. 6 , 11 , 16 In addition to the nature of the lesion, massive hemorrhage in the limited lumen of the duodenum can be overlooked because of other concomitant lesions such as an ulcer, and an inexperienced endoscopist who looks for an inflammed lesion can overlook the DL because of clots, duodenal angulations, or periampulary diverticulum. Thus, the duodenal DL cannot always be controlled on the first attempt.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, multiple endoscopies are often necessary to make the diagnosis. 6 , 11 , 16 In addition to the nature of the lesion, massive hemorrhage in the limited lumen of the duodenum can be overlooked because of other concomitant lesions such as an ulcer, and an inexperienced endoscopist who looks for an inflammed lesion can overlook the DL because of clots, duodenal angulations, or periampulary diverticulum. Thus, the duodenal DL cannot always be controlled on the first attempt.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Lopez-Arce et al showed that patients underwent at least 3 attempts to control the duodenal DL bleedings. 16 To overcome this problem, early endoscopic evaluation and side-viewing endoscopy is needed. 17 , 18 Endoscopies performed within the first 12 hours have a high success rate for diagnosing DLs because of their capability to pinpoint the bleed location.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Dieulafoy's lesions can be asymptomatic; however, lesions with acute, profound bleeding require medical attention. Most patients with gastric lesions present with hematemesis or melena, whereas colonic and rectal lesions are characterized by bright red bleeding per rectum [8]. Transfusion-dependent severe anemia and hemodynamic instability can occur rapidly and are attributed to the arterial nature of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion-dependent severe anemia and hemodynamic instability can occur rapidly and are attributed to the arterial nature of the vessel. In a case series involving 20 patients with Dieulafoy's lesions, about 50% presented to the hospital with hemodynamic instability as the presenting symptom [8]. Occult GI bleeding and chronic anemia are very rarely associated with these lesions [9].…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this century, the first perspective randomized-controlled study demonstrated that hemoclip and band ligation are equally effective compared to injection therapy for DL bleeding [ 4 ]. The overall hemostasis rate in hemoclip therapy has been shown to be up to 95% [ 5 ], but the ratio of emergent surgery is still above 5%, according to a recent multicenter report [ 6 ]. Furthermore, currently, there are no cohort studies on the effectiveness of cyanoacrylate injection for the treatment of duodenal DLs, since most of DLs are located in a proximal stomach.…”
Section: Introductionmentioning
confidence: 99%